The Influence of Partnership Patterns on Improving Inter-Island Transportation Service Productivity in the Archipelagic Region of Makassar City - Makmur, Makmur; Poerwanto, Poerwanto; Syawaluddin, Ahmad; Rohman, Moh. Aziz (PINISI Discretion Review, 2025)
The purpose of the study was to examine partnership patterns in increasing the productivity of inter-island transportation services in the Sangkarrang District archipelago. The method used descriptive qualitative and quantitative analysis, considering the empirical perceptions of transportation users, operators, regulators and also the public to be able to explain how the existence of the marine transportation service system in the Makassar archipelago. The sample was selected based on the criteria of population, area and potential of the region, using probability sampling with cluster random sampling to determine the potential conditions and economic activities of the community. Field physical studies and quantitative statistics were conducted to explain the conditions. The results of the study showed that partnership patterns involving the government, the private sector, and local communities have proven to be able to increase the efficiency, accessibility, and quality of transportation services. Forms of partnerships such as operational management, investment, and training have proven to have a direct impact on increasing the frequency of trips, more regular ship maintenance, and increasing the capacity and quality of human resources.